Pengaruh Harga dan Kualitas Layanan terhadap Loyalitas Pelanggan Bengkel Motor GnR - Prehatsari, Ferika; Syihabuddin, Muhammad (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The purpose of this study is to find out how price and service quality affect customer loyalty of GnR Motorcycle Repair Shop. One hundred customers of the GnR Motor Repair Workshop filled out a questionnaire as part of the quantitative techniques used in this study. Using SPSS software, the data was analyzed using multiple linear regression. The results show that pricing has a positive and significant impact on customer loyalty, with higher levels of customer loyalty associated with prices that are considered more reasonable. In addition, service quality, especially in terms of reliability, punctuality, and customer service, also has a positive and significant impact on customer loyalty. These findings suggest that customer loyalty is strongly influenced by a combination of competitive pricing and consistent service quality. Therefore, GnR Motorcycle Workshop needs to find the optimal balance between affordable pricing and improving service standards to retain consumers and increase business competitiveness in the future.